2019
DOI: 10.1002/jcp.29148
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture induces adenosine in fibroblasts through energy metabolism and promotes proliferation by activating MAPK signaling pathway via adenosine3 receptor

Abstract: Acupuncture has many advantages in the treatment of certain diseases as opposed to drug therapy. Besides, adenosine has been revealed to affect cellular progression including proliferation. Therefore, this study aimed at exploring the mechanism involving acupuncture stress and adenosine in fibroblast proliferation. The fibroblasts from fascia tissues of the acupoint area (Zusanli) were stimulated by different levels of stress, different concentrations of adenosine, and agonist or antagonist of A 3 receptor (A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Upon activation of the A 3 receptor, (1) the Gα subunit may dissociate from its G βγ , decreasing the catalytic activity of adenylyl cyclase and cyclic AMP production, (2) phospholipase C is activated, leading to Ca 2+ increase or PI3K, Akt phosphorylation, (3) G protein RhoA and phospholipase D are stimulated, (4) mitogen-activated protein kinase (MAPK) family, such as extracellular regulated kinases (ERKs), MAPK-interacting kinase (MNK), and p38, are modulated, and (5) K ATP channels are opened; downstream these pathways, are a series of transcription factors, such as the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), the cAMP response element-binding protein (CREB), the hypoxia-inducible factor 1-alpha (HIF-1α), and the c-myc (reviewed in [18]). Mechanical loading of rat subcutaneous fibroblasts increases adenosine levels and upregulates A 3 receptors expression and signaling through the MAPK signaling pathway, resulting in modification of cells proliferation and immune-related factors production [49]. Among the MAPK family, which is subdivided into extracellular regulated kinases, such as ERK1/2, and stress-activated protein kinases (SAPK), such as p38 and jun-N-terminal kinase (JNK), the ERK1/2 seems to represent the preferential pathway for cell division and proliferation responses.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation of the A 3 receptor, (1) the Gα subunit may dissociate from its G βγ , decreasing the catalytic activity of adenylyl cyclase and cyclic AMP production, (2) phospholipase C is activated, leading to Ca 2+ increase or PI3K, Akt phosphorylation, (3) G protein RhoA and phospholipase D are stimulated, (4) mitogen-activated protein kinase (MAPK) family, such as extracellular regulated kinases (ERKs), MAPK-interacting kinase (MNK), and p38, are modulated, and (5) K ATP channels are opened; downstream these pathways, are a series of transcription factors, such as the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), the cAMP response element-binding protein (CREB), the hypoxia-inducible factor 1-alpha (HIF-1α), and the c-myc (reviewed in [18]). Mechanical loading of rat subcutaneous fibroblasts increases adenosine levels and upregulates A 3 receptors expression and signaling through the MAPK signaling pathway, resulting in modification of cells proliferation and immune-related factors production [49]. Among the MAPK family, which is subdivided into extracellular regulated kinases, such as ERK1/2, and stress-activated protein kinases (SAPK), such as p38 and jun-N-terminal kinase (JNK), the ERK1/2 seems to represent the preferential pathway for cell division and proliferation responses.…”
Section: Discussionmentioning
confidence: 99%
“…Following the application of P38/ MAPK specific inhibitors to cells, it was found that ADMD significantly inhibited cytoskeletal remodeling, revealing that P38/MAPK plays an important role in the process of cytoskeletal remodeling induced by ADMD. Acupuncture as a mechanical stimulation at "Zusanli" acupoint induces the increase of adenosine in fibroblasts through the activation of the MAPK signaling pathway, ultimately promoting fibroblast proliferation [27].…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of EA, such as waveforms, frequencies, intensity, and stimulus time, can be accurately characterized. It is reported that acupuncture has positive effects on the central nervous system (15), metabolism (16), gastrointestinal system (17), and immune system (18), and in the treatment of obesity. Acupuncture may bring about weight loss by regulating appetite and energy expenditure (19).…”
Section: Introductionmentioning
confidence: 99%